Prospect of composite tubes based on bi-materials for weight reduction of vehicles - Abbas, T. (Springer Singapore, 2019)
This chapter provides a study related to energy absorption and failure modes of thin-walled tubes under axial compression. The study was to focuses on partial wrapping of light-weight thin-walled aluminium tube with glass/epoxy, which is very significant to enhance the safety of automobiles. Partially wrapped aluminium tube samples have been prepared according to the L9 Taguchi design orthogonal array, by applying various fiber orientations, composite layers and partially wrapped area via filament winding process. The study revealed that the optimum combination of fiber orientation, composite layers, and the partially wrapped area was ± 55°, 6, and 30 respectively. This combination was achieved via the analysis of variance (ANOVA), and the main plot effect analysis. Moreover, this combination also has 81.92, and 62.08 higher values of specific energy absorption (SEA), and 47.67 and 1.54 more values of crush force efficiency (CFE) as compared to the simple aluminium tube and its predecessor the steel tube, respectively. The results show the two-lobe diamond failure mode of this combination (±55°, 6, and 30). The findings demonstrate the ability of the approach as a reliable and light-weight solution for energy absorbers with a high value of SEA and CFE. © Springer Nature Singapore Pte Ltd. 2020.